Удосконалення обліку дебіторської заборгованості у контексті формування інформаційного забезпечення управління платоспроможністю суб’єкта господарювання - Kuz, Vasyl; Popova, Valentina (Класичний приватний університет, 2020)
У статті розглянуто особливості формування інформаційного забезпечення управління платоспроможністю суб’єкта господарювання у частині аналітичних даних про дебіторську заборгованість. Доведено необхідність поділу дебіторської заборгованості покупців і замовників за термінами погашення та за ймовірністю неповернення, що забезпечить можливість організації аналітичного обліку за наведеними класифікаційними ознаками. Визначено перелік кореспонденцій рахунків з аналітичного обліку дебіторської заборгованості, які нададуть можливість облікового відображення нормальної, сумнівної та безнадійної заборгованості за термінами погашення (термінами прострочення платежів), а також забезпечать перспективи, у рамках облікового процесу, формування показників управлінської бухгалтерської звітності як елементів інформаційного забезпечення управління платоспроможністю суб’єкта господарювання. Adherence of the acceptable level of solvency is one of the most important tasks of long-term economic activity and the results of effective management. Management decisions in the sphere of ensuring solvency of the entity certainly leads to the operation of settlement transactions data, which in terms of orientation of the accounting system on the indicators of financial statements necessitates analytical submission of information about receivables by management staff. In the article was considered special features of the formation of information support of solvency management by entity in terms of analytical data about receivables. The necessity of division of receivables of buyers and customers by terms of repayment (up to 10 days; from 10 days to 30 days; from 30 days to 60 days; from 60 days to 180 days; from 180 days to 360 days) and by probability of non-repayment was proved (normal receivables (repayment will take place in accordance with the terms stipulated in the contract); doubtful receivables (there is a possibility of non repayment for various reasons); bad receivables (there is non-repayment), which will provide the possibility of organization of analytical accounting on the basis of classification. The list of correspondence accounts from analytical accounting of receivables was identified which will give the chance of accounting reflection of normal, doubtful and bad receivables in terms of repayment (terms of overdue payments), and also provide, within the accounting process, the prospects for the formation of indicators of management accounting statements as elements of information support for solvency management of the entity. There is a need to follow the principles of analogy in the organization of analytical accounting of payables for goods (works, services), which will ensure the formation of a holistic data set for solvency management, and also will create the preconditions for strengthening the performance of control and analytical functions by management staff on the basis of accounting data, which can be systematized and generalized in the necessary analytical sections.
Improving of the accounting of receivables in the context of the formation of information support for solvency management of the entity
Keywords: аналітичний облік; бухгалтерські рахунки; дебіторська заборгованість; інформаційне забезпечення; платоспроможність; управлінські рішення; analytical accounting; accounts, receivables; information support; solvency; management decisions